Factor analysis of the improvement of bat energy in baseball hitting - Yang, C; Jin, P. (Journal of Human Sport & Exercise, 2025)
Baseball hitting involves multiple biomechanical variables, and understanding their impact on bat energy is crucial for improving performance. However, no studies have explored how biomechanical features affect hitting performance from the perspective of bat energy. This study aimed to systematically investigate the influence of lower limb biomechanical variables on bat energy using factor analysis and stepwise regression methods. Sixteen right-handed baseball players participated in the study. Bilateral lower limb kinematic and kinetic features were calculated and exported using a motion capture system and force platform. Six key factors (F1-F6) were extracted from the 28 biomechanical features. Factors F1 and F5 are correlated with the rotation of the trailing and leading limbs, respectively; F2 correlates with energy production of the leading limb; F3 correlates with linear momentum production; F4 correlates with body posture control; and F6 correlates with body linear movement in the anterior direction. To enhance bat energy, hitters should step towards the incoming ball more rapidly to increase ground reaction force on the leading limb. They should also maximize extension and external rotation of both the leading and trailing limbs, stabilize the trailing limb during body rotation, and ensure proper weight distribution between the leading and trailing limbs.